Mass Spectrometry Imaging: Revolutionizing Molecular Insights in Infectious Diseases Research - Minmin Zhang; Xiao Wang; Xiaoling Su; Aidiya Yimamu; Lanjuan Li; Zeyu Sun (Pathogens, 2025)
Infectious diseases remain a leading cause of mortality worldwide. The pathogenesis that comprises infection, focal inflammation, and immuno-response, typically occurs in one or multiple organs or tissues. Analysis of the molecular composition of affected tissues with their spatial context is pivotal to elucidate the underlying disease mechanisms and to develop accurate diagnostic strategies. In recent years, mass spectrometry imaging (MSI) technology has achieved significant advancements and has emerged as an powerful tool for tissue-based molecular exploration with high molecular specificity and spatial resolution. Although MSI has been rapidly adopted in numerous branches of biomedical research, its application in the field of infectious diseases research is still in its early stages. With this in mind, this review aims to familiarize infectious disease researchers with the advantages and diverse applications of MSI. Additionally, we delineate several existing technical challenges, application pitfalls, and the potential solutions to overcome these challenges.